Digital Ethnographic Exploration of Media Narratives: Shaping Investment Decisions in Halal Tourism Ecosystems - Singgalen, Yerik Afrianto (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This research investigates the influence of digital media narratives on investment decision frameworks within halal tourism ecosystems through digital ethnographic methodology. The study employs a comprehensive methodological approach incorporating systematic data collection across multiple digital platforms, including specialized forums, social media environments, and digital financial communities. Using mixed-methods analysis combining qualitative narrative assessment with quantitative lexicometric evaluation, the research reveals significant patterns in terminology frequency, with tourism-related terms dominating the discourse at 17,181 instances, followed by growth indicators (5,587), value measurements (4,678), and impact assessments (4,524). The business environment analysis identifies "tourism" as the predominant term (174 occurrences), followed by "muslim" (127) and "halal" (93), demonstrating fundamental market dynamics. Digital ethnographic analysis illuminates distinctive patterns in investment behavior through three interconnected phases: initial digital immersion, targeted observation of investor-content interactions, and in-depth narrative reception analysis. The findings demonstrate that digital media narratives fundamentally influence investment decisions through sophisticated platform interactions, with distinctive patterns emerging at intersections of Islamic principles and economic considerations. This research contributes to understanding investment dynamics within halal tourism markets while establishing robust parameters for culturally sensitive market development.